2013
DOI: 10.1515/hsz-2013-0162
|View full text |Cite
|
Sign up to set email alerts
|

Structural comparison of the transport units of type V secretion systems

Abstract: Pathogenic gram-negative bacteria have evolved several secretion mechanisms to translocate adhesins, enzymes, toxins, and other virulence factors across the inner and outer membranes. Currently, eight different secretion systems, type I-type VIII (T1SS-T8SS) plus the chaperone-usher (CU) pathway, have been identified, which act in one-step or two-step mechanisms to traverse both membrane barriers. The type V secretion system (T5SS) is dependent first on the Sec translocon within the inner membrane. The peripla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…It is controversially discussed whether a partially folded passenger can be translocated across the outer membrane. Two mechanisms for translocation—the hairpin model and the Omp85 model—have been proposed whereas only the latter would be compatible with partial protein folding [ 10 ]. We observed that heme derived from cells is way more effective for increasing CYP activity than externally added heme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is controversially discussed whether a partially folded passenger can be translocated across the outer membrane. Two mechanisms for translocation—the hairpin model and the Omp85 model—have been proposed whereas only the latter would be compatible with partial protein folding [ 10 ]. We observed that heme derived from cells is way more effective for increasing CYP activity than externally added heme.…”
Section: Discussionmentioning
confidence: 99%
“…As a biotechnological tool for surface display of recombinant proteins so-called autotransporters have been widely employed [ 9 ]. They are derived from natural outer membrane proteins in gram-negative bacteria and their translocation mechanism and structure have been intensively studied [ 10 14 ]. The technique has been successfully applied for the display of a variety of enzymes such as nitrilase [ 15 ], lipase and foldase [ 16 ], protein kinase CK2 [ 17 ] as well as other proteins like V HH antibody fragments [ 18 ], affibodies [ 19 ] and peptides [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reviews by Lenders et al (2013) and Gawarzewski et al (2013) summarize structural and functional data that provide molecular insights into the Type I and Type V secretion systems, respectively. Sch ü nke and Stoldt (2013) describe structural insights about cyclic nucleotide-binding induced conformational changes in cyclic nucleotidebinding domains (CNBDs) and their potential coupling with channel gating.…”
Section: Summarize Recent Progress In Understandingmentioning
confidence: 99%
“…The T4SS has been shown to transport nucleic acids in addition to complex proteins (Christie et al, , 2014. T5SSs can be divided into five subclasses (a-e): the T5aSS is an autotransporter (AT), the T5bSS is a two-partner secretion (TPS) system, the T5cSS is the trimeric AT, the T5dSS is a fusion between AT and TPS, and finally the T5eSS is the inverted AT (Gawarzewski et al, 2013;Leo et al, 2012). They have been shown to be required for virulence in Haemophilus influenzae, Yersinia enterocolitica, Neisseria gonorrhoeae, Helicobacter pylori and Bordetella pertussis (Bernstein, 2007;Dautin & Bernstein, 2007;Henderson et al, 2004;Jacob-Dubuisson et al, 2004;Marr et al, 2008;Noofeli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%